Results of disseminating an online screen for eating disorders across the U.S.: Reach, respondent characteristics, and unmet treatment need. Issue 6 (13th February 2019) - Fitzsimmons‐Craft, Ellen E.; Balantekin, Katherine N.; Graham, Andrea K.; Smolar, Lauren; Park, Dan; Mysko, Claire; Funk, Burkhardt; Taylor, C. Barr; Wilfley, Denise E.
Abstract: Objective: The treatment gap between those who need and those who receive care for eating disorders is wide. Scaling a validated, online screener that makes individuals aware of the significance of their symptoms/behaviors is a crucial first step for increasing access to care. The objective of the current study was to determine the reach of disseminating an online eating disorder screener in partnership with the National Eating Disorders Association (NEDA), as well to examine the probable eating disorder diagnostic and risk breakdown of adult respondents. We also assessed receipt of any treatment. Method: Participants completed a validated eating disorder screen on the NEDA website over 6 months in 2017. Results: Of 71, 362 respondents, 91.0% were female, 57.7% 18–24 years, 89.6% non‐Hispanic, and 84.7% White. Most (86.3%) screened positive for an eating disorder. In addition, 10.2% screened as high risk for the development of an eating disorder, and only 3.4% as not at risk. Of those screening positive for an eating disorder, 85.9% had never received treatment and only 3.0% were currently in treatment. Discussion: The NEDA online screen may represent an important eating disorder detection tool, as it was completed by >71, 000 adult respondents over just 6 months, the majority of whom screened positive for a clinical/subclinical eating disorder. The extremely high percentage of individuals screening positive for an eating disorder who reported not being in treatment suggests a wide treatment gap and the need to offer accessible, affordable, evidence‐based intervention options, directly linked with screening.